THE KHOREZM SCHOOL OF ARABIC LINGUISTICS AND THE SCHOLARLY LEGACY OF NASIR AL-MUTARRIZI - Diyora Abdurayimova (International Journal of Literature and Language Studies, 2026)
This study examines the emergence and development of Arabic linguistic scholarship in Khorezm and Transoxiana and analyzes the intellectual legacy of Nasir al‑Mutarrizi. Following the spread of Islam, Arabic became the principal language of religion, scholarship, and administration. As a result, scholars of Central Asia devoted considerable attention to grammar, lexicography, rhetoric, and literary studies. Khorezm emerged as one of the most influential centers of Arabic learning and produced generations of linguists whose works enriched the Arabic grammatical tradition. The article surveys the contributions of major Khorezmian scholars, including al‑Khwarizmi, al‑Biruni, al‑Tabarkhazi, al‑Barqani, Abu Mudar, and al‑Khirasi. Special attention is devoted to al‑Mutarrizi’s life, education, teachers, students, and linguistic writings. The study concludes that the Khorezm school played a decisive role in preserving and developing Arabic linguistic sciences in the medieval Islamic world.